Risankizumab in Severe Asthma — A Phase 2a, Placebo-Controlled Trial - Brightling, Christopher E; Nair, Parameswaran; Cousins, David J; Louis, Renaud; Singh, Dave (The New England journal of medicine, 2021)
Although interleukin-23 has been implicated in the pathogenesis of asthma, in this randomized, controlled trial involving adults with severe asthma, inhibition of interleukin-23 signaling with the monoclonal antibody risankizumab resulted in worse asthma outcomes than placebo.